Pengaruh Model Reciprocal Teaching terhadap Hasil Belajar Fisika Siswa pada Pokok Bahasan Pemanasan Global - I Putu Kusuma Yuda; Amiruddin Hatibe (Jurnal Kreatif Online, 2021)
The study aimed to determine whether there was an effect of the Reciprocal Teaching model on students' physics learning outcomes on the topic of global warming. The method was quasi-experimental and the research design was the equivalent pretest-posttest group design. The population of this study was all seventh-grade students of SMP Negeri 13 Sigi. The sampling technique was purposive sampling. The research sample was class VII A (n = 24) as the experimental group and class VII C (n = 24) as the control group. The research instrument was a test of physics learning outcomes in multiple-choice. The test of physics learning outcomes obtained showed that the average score of the experimental group was 15.08 higher than the control class, which was 12.62. The t-test hypothesis (two-tailed) was obtained tcount = 5.01 and ttable = 2.01 at the significance level α = 0.05. This result means that the value of tcount is outside the receiving area of ​​H0, thus H0 is rejected and H1 is accepted. In other words, there are differences in physics learning outcomes between the experimental group and the control group. So, it can be concluded that there is an effect of the Reciprocal Teaching model on student physics learning outcomes on the topic of global warming.